2014
DOI: 10.1093/ajh/hpu119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aliskiren on Circulating Endothelial Progenitor Cells and Vascular Function in Patients With Type 2 Diabetes and Essential Hypertension

Abstract: Aliskiren had a favorable effect on endothelial function and EPCs, reduced arterial stiffness, and improved LV twisting and untwisting. These effects were independent of BBP lowering, as they were not observed after the achievement of similar values of BBP with HCTZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
1
29
0
4
Order By: Relevance
“…Previous studies have shown that aliskiren can increase the number of EPCs in the context of atherosclerosis in hypercholesterolemic mice [35], and in patients with type 2 diabetes and hypertension [36]. However, the potential role of aliskiren to modulate EPCs in the setting of ischemia-induced neovascularization has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that aliskiren can increase the number of EPCs in the context of atherosclerosis in hypercholesterolemic mice [35], and in patients with type 2 diabetes and hypertension [36]. However, the potential role of aliskiren to modulate EPCs in the setting of ischemia-induced neovascularization has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The AQUARIUS study, which analyzed the effects of the drug in prehypertensive individuals with coronary atherosclerosis, concluded that it did not offer any additional benefit to patients (Nicholls et al, ). However, many studies reported beneficial effects of ALI in regard to endothelial function and arterial rigidity (Bonadei et al, ; Fukutomi, Hoshide, Mizuno, & Kario, ; Raptis et al, ). Furthermore, it reduces ventricular mass according to the ALLAY study, which revealed that ALI is as effective as losartan in the reduction of hypertrophied ventricular mass in hypertensive patients with BMI >25 kg/m 2 (Solomon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible benefits of ALI on other physiological targets, such as endothelial function and arterial stiffness, on which recent studies have suggested favorable effects [108,109,110] warrant further investigation. Also, the exact clinical implications in the role of disease of the (pro)renin receptor and PRA levels should be established, as ALI has an effect on both.…”
Section: Discussionmentioning
confidence: 99%